Jinian Mao zhuxi changyou Changjiang yi zhounian - Genzhe Mao zhuxide zai dafeng dalang zhong qianjin! (1967)
'Commemorate the first anniversary of Chairman Mao's swim over the Yangzi - Follow Chairman Mao in moving forward in wind and waves!'